The Experimental Study of the Influence of Modal to the Noise of the Hydrofoil. Issue 4 (March 2020) - Xu, Yingbo; Tang, Denghai
Abstract: In order to study the influence of modal to the noise of the blade, the tests of modal and noise are carried out in the cavitation tunnel. The modal of hydrofoil was measured in the water and the noises of the hydrofoil with different inflow velocity were tested. The results show that the frequency of the peak of the noise spectrum is not changed with the inflow speed increasing. The amplitude of the peak increases first and then decreases with the inflow speed increasing. The structural characteristic of the hydrofoil has important influence on the noise and the frequency of the peak is equal to the modal frequency.